2009
DOI: 10.1099/vir.0.011478-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seven novel human papillomavirus types isolated from cutaneous tissue, but also present in mucosal lesions

Abstract: Seven novel human papillomavirus (HPV) types were isolated and characterized. HPV 94 is related most closely to HPV 10 and belongs to the genus Alphapapillomavirus, whereas HPV 98, HPV 99, HPV 100, HPV 104, HPV 105 and HPV 113 all belong to the genus Betapapillomavirus. These HPV types were isolated from and demonstrated in cutaneous tissue, but HPV 98, HPV 100, HPV 104 and HPV 113 were also detected in malignant oesophageal and oral lesions. The general prevalence of these HPV types in lesions is infrequent.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 38 publications
1
91
0
1
Order By: Relevance
“…Recent studies have shown that oral infection with HPVs is associated with a significant risk of developing oropharyngeal cancer and OPMDs 10,20,21) . Although HPV infection has been detected in OLP tissue 11,20,[22][23][24][25] and HPV DNA is detected in OLP tissue more often than in normal oral mucosa 11,19) , there is no firm evidence as yet that HPV is a causative factor of oral cancer. The objective of the present investigation was to assess HPVgenotype distribution in OLPs of Japanese patients and also to clarify the relationship between malignant transformation in OLP and HPV infection using PCR, in situ hybridization, and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that oral infection with HPVs is associated with a significant risk of developing oropharyngeal cancer and OPMDs 10,20,21) . Although HPV infection has been detected in OLP tissue 11,20,[22][23][24][25] and HPV DNA is detected in OLP tissue more often than in normal oral mucosa 11,19) , there is no firm evidence as yet that HPV is a causative factor of oral cancer. The objective of the present investigation was to assess HPVgenotype distribution in OLPs of Japanese patients and also to clarify the relationship between malignant transformation in OLP and HPV infection using PCR, in situ hybridization, and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Over 120 types of HPVs have been identified to date 19) . HPVs have been divided into low-risk (LR) and high-risk (HR) groups based on the clinical behavior of the virally infected tissues.…”
Section: Introductionmentioning
confidence: 99%
“…They are classified by family, genus, species and types according to several criteria. More precisely, types are determined on the basis of sequence homology to the gene encoding the L1 protein, which is the most conserved gene in the HPV genome (Aubin et al, 2007;de Villiers et al, 2004;de Villiers & Gunst, 2009). The genotypes are also more commonly used to refer the different types.…”
Section: Risk Factors For the Development Of Hnsccmentioning
confidence: 99%
“…They are classified by family, genus, species and types according to several criteria. More precisely, types are determined on the basis of sequence homology to the gene encoding the L1 protein, which is the most conserved gene in the HPV genome (Aubin et al, 2007;de Villiers & Gunst, 2009). The genotypes are also more commonly used to refer the different types.…”
Section: Hnscc and Hpv: Incidence Biological Pathways And Impact On mentioning
confidence: 99%